The Factors Influencing Nanotechnology Strategy in Malaysian Industries - Elley Nadia, Elliazir (2009)
The worldwide nanotechnology research and development (R&D) investment reported by organizations has increased. At least 30 countries have initiated, or are beginning national activities in this field. Industry has gained confidence that nanotechnology will bring competitive advantage. The worldwide annual industrial production is estimated to exceed $1 trillion in 10-15 years from now. which would require about 2 million nanotechnology workers. Since the emergence of this new technology, Malaysia has succeeded in officially launching the Malaysian Nanotechnology Initiatives with the mission: nanotechnology for sustainable national development of science, technology, industry and economy. To further engage in nanotechnology, this research aims to identify the current state of nanotechnology development and the current support mechanism availability in Malaysia. There are 7 key factors in determining the Malaysian Strategy in both short-term and long-term periods in this field. These are external forces. human resource, technical issues, internal issues. technology partnership. knowledge and culture. The findings in this research revealed that the infrastructure and central facilities for nanotechnology is not adequate for the technology to thrive in. There are 59.5% dedicated laboratories, specialized equipment only 16.75% with nanotechnology center of excellent only 9.5%. The most significant variables that shows strongest relationship in short-term strategy is technology partnership (73.6%), followed by internal issue (64.4%). knowledge(61.5%), human resource (28.9%), external forces (27.8%), technical issue (22.6%) and finally culture (11.6%). The result on long-term strategy shows that Technology partnership (46.7%). Knowledge (52.1 %), external forces (41.8%), human resource (30.5%), technology partnership (27.1%), internal issue (26.1 %) and culture (6.1 %). The multiple regression result on both short-term and long-term strategy shows that technology partnership shows a significant strong relationship with 73.5%, followed by internal issue (55.3%) and knowledge (55.3%). external forces 39.7%, human resource (35.2%), technology partnership (29.2%) and culture (10.9%). Since this research is more comprehensive in terms of identifying all the key factors for managing nanotechnology in Malaysian industries, hopefully the findings will benefits all stakeholders and for future direction in this technology.